Primulina minima, a new species of cave-dwelling Gesneriaceae from the karst landscape of northwestern Guangxi, China - Long, Shu-Ting; Xin, Zi-Bing; Maciejewski, Stephen; Fu, Long-Fei (Phytotaxa, 2025)
A new cave-dwelling species of Gesneriaceae, Primulina minima Z.B.Xin & L.F.Fu, endemic to Fengshan County, Guangxi, China, is described and illustrated. Closely related to P. longzhouensis (B.Pan & W.H.Wu) W.B.Xu & K.F.Chung, It also resembles Primulina rufipes Y.L.Su, P.Yang & Y.Liu and P. huaijiensis Z.L.Ning & J.Wang, it can be distinguished by a unique combination of morphological characters. These include the number of inflorescences, bract length, corolla length and tube shape, petal apex, and ovary size. Currently, P. minima is known only from a single large cave in the type locality, with a population estimated to be fewer than 50 mature individuals. Based on the IUCN assessment standards, the conservation status of this species is provisionally assessed as Critically Endangered [CR+C2a (i)].